Genocide of the Soviet People in German Occupation Policy: Civilizational Perspective on the "War of Extermination" - Bagdasaryan, Vardan E.; Resnyansky, Sergey I. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Istoriâ Rossii (Print), 2025)
The authors examine the historical grounds for assessing the policy of Germany and its allies in the occupied territory of the USSR as a purposeful genocide of the Soviet people. The key research method in-volved correlating empirical material of mass atrocities and plans of the Nazis with the definition of genocide as outlined in the “Convention on the Prevention and Punishment of the Crime of Genocide” adopted by the UN General Assembly in 1948. The novelty of the problem consists in the assertion of the thesis that the genocide against the Soviet people should be considered an integral issue to the civilized international community. The article presents arguments for the expediency and reliability of recognizing the genocide not only in ethnic, but also in civilizational terms. The approaches formulated in the article could potentially contribute to the adoption of a legal provision recognizing the genocide of the Soviet people and holding those responsible accountable at the legislative level of the Russian Federation.